Capsule enteroscopy versus small-bowel ultrasonography for the detection and differential diagnosis of intestinal diseases - Luca Elli; Erica Centorrino; Andrea Costantino; Maurizio Vecchi; Stefania Orlando; Mirella Fraquelli (Clinical Endoscopy, 2022)
Background/Aims Capsule enteroscopy (CE) and intestinal ultrasonography (IUS) are techniques that are currently used for investigating small-bowel (SB) diseases. The aim of this study was to compare the main imaging findings and the lesion detection rate (LDR) of CE and IUS in different clinical scenarios involving the SB. Methods We retrospectively enrolled patients who underwent CE and IUS for obscure gastrointestinal bleeding (OGIB), complicated celiac disease (CeD), and suspected or known inflammatory bowel disease (IBD). We evaluated the LDR of both techniques. The accuracy of IUS was determined using CE as the reference standard. Results A total of 159 patients (113 female; mean age, 49±19 years) were enrolled. The LDR was 55% and 33% for CE and IUS (p<0.05), respectively. Subgroup analysis showed that the LDR of CE was significantly higher than that of IUS in patients with OGIB (62% vs. 14%, p<0.05) and CeD (55% vs. 35%, p<0.05). IUS showed a similar LDR to CE in patients with suspected or known IBD (51% vs. 46%, p=0.83). Conclusions CE should be preferred in cases of OGIB and CeD, whereas IUS should be considered an early step in the diagnosis and follow-up of IBD even in patients with a proximal SB localization of the disease.